Retention of Adult Distance Education Students Through the Use of Student Support Services - Wilson, Kristy (East Carolina University)
Adult learners are returning to colleges to complete degrees in higher rates, while also balancing work, caregiving and other responsibilities. These students look to online education as a way to balance conflicting demands. The purpose of this study was to explore the unique needs of this student demographic in relation to student support services offered by the university as a means of student retention. This study is rooted in Tinto's theory of student integration and model of student departure and Knowles' principles of andragogy which suggest adult students know why they are enrolled in courses, have a distinct goal in mind, and look to faculty interaction to achieve those goals. This study used a qualitative inquiry approach and, more specifically, emergent design to examine the various needs of adult students within both distance education and distance continuing education programs through student surveys and semi-structured interviews. Data collection and analysis allowed for the exploration of student support services and the impact these services have on the retention of adult learners in distance education programs. Results of the study provided insights as to the greatest needs of adult online learners and what may have the greatest impact on their ability to successfully complete their program of choice; including what was beneficial to their goals such as faculty interaction and family support. The results of the study also allowed for recommendations to be provided to improve services and retention of adult students. This study provides an opportunity for further research concerning stop-out of adult learners and specific hardships that prevent adult learners from completing their academic goals. Once specific supports can be identified and made available, the institution can re-evaluate current services and determine ways to continue supporting adult online learners.
Keywords: Adult college students; College dropouts--Prevention; Web-based instruction; Student assistance programs; Distance education students